Influence Hedonic Life Style And Customer Experience On Customer Loyalty With Customer Loyalty As An Intervening Variable - Sutedjo , Bambang; Sumiyati , Sri (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
Hearing the word Starbucks Coffee, people must know company shop coffee the biggest in world Which positioned as a coffee shop for the upper economic class as a lifestyle. The research conducted has the aim of analyzing the influence of hedonic lifestyle and customer experience on Customer Loyalty with the mediation variable Customer Satisfaction on Starbucks coffee customers, it is hoped that the research conducted can provide an overview of the hedonistic lifestyle and consumer experience in enjoying Starbucks coffee. The research conducted using a sample of Starbucks coffee consumers in the city of Semarang which has 14 coffee outlets, with 60 respondents with a purposive sampling technique, by distributing questionnaires via Google Form. The analysis technique uses an instrument test in the form of a validity and reliability test, while the data processing technique uses multiple regression analysis. The results of the study show that the hedonic lifestyle and customer experience variables have a positive influence on Customer Satisfaction and Customer Loyalty , mediation testing shows that the customer satisfaction variable is not a mediating variable, only a reinforcing variable.